Future prevalence of type 2 diabetes in Germany: a projection until 2040 including incidence trends observed during the SARS-CoV-2 pandemic - Tönnies, T.; Voeltz, D.; Voß, S.; Hoyer, A.; Brinks, R. (Frontiers in Epidemiology, 2025)
IntroductionPrevious studies indicate that the prevalence of type 2 diabetes (T2D) will increase substantially over the coming decades. One projection from 2019 estimated an increase in prevalence in Germany by 54% to 77% (depending on future trends in incidence and mortality) between 2015 and 2040. We aim to update this projection by incorporating recently published trends in T2D incidence in Germany that include the changes during the SARS-CoV-2 pandemic.Materials and methodsWe used a partial differential equation that describes the illness-death model to project the age- and sex-specific T2D prevalence among adults between 2015 and 2040. This required input data for the age- and sex-specific incidence, mortality of the general population, mortality rate ratio of people with vs. without T2D and prevalence in the initial year of the projection. We considered five scenarios with different future trends in incidence and their impact on prevalence. Using the most recently available data on T2D incidence, we assumed that the incidence remains constant as observed in 2021 for the whole projection horizon (first scenario). In further scenarios, we assumed that the observed age- and sex-specific trends in incidence between 2015 and 2021 would continue until 2025 (second scenario), 2030 (third scenario), 2035 (fourth scenario) and 2040 (fifth scenario). One additional scenario assumed that the age-specific prevalence remains constant.ResultsObserved trends in incidence suggest a decrease between 2015 and 2017, and a slight upward trend thereafter until 2021 in most age groups. Depending on how long these observed increases in incidence continue, the number of people with T2D in Germany will increase from 6.8 million in 2015 to between 10.9 million and 14.2 million in 2040. These numbers correspond to increases in prevalence from 10.5% in 2015 to between 15.5% and 20.1% in 2040. In the constant prevalence scenario, the overall prevalence and number of people with T2D in 2040 was 11.4% and 8.1 million, respectively.ConclusionsThe future prevalence of T2D in Germany strongly depends on how long the recently observed increasing trend in T2D incidence will continue, which warrants close monitoring of these trends in post-pandemic years.